2007
DOI: 10.1681/asn.2006050514
|View full text |Cite|
|
Sign up to set email alerts
|

Oxidized Low-Density Lipoproteins Activate CD4+ T Cell Apoptosis in Patients with End-Stage Renal Disease through Fas Engagement

Abstract: Oxidized LDL (oxLDL) are cytotoxic to vascular cells, but their possible toxic action on T cells from patients with ESRD has not been evaluated. oxLDL concentrations were measured and compared in patients who were on long-term hemodialysis (HD), in patients who had ESRD and were on continuous ambulatory peritoneal dialysis, in nondialyzed patients with chronic kidney disease, and in age-and gender-matched control subjects. In parallel, the proliferative capacity of CD69

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 37 publications
4
30
0
Order By: Relevance
“…1,2 Abnormal lipoprotein metabolism has been implicated as a possible cause of these complications because of its potential role in immune system activation. [3][4][5][6] Cumulative data based on atherosclerotic experimental models suggest that CD4 ϩ T cells are present within plaques from initial stages of the disease. [7][8][9] They are mainly CD4 ϩ T-helper cells with a phenotype characteristic of the proinflammatory T-helper 1 (Th1) subset.…”
mentioning
confidence: 99%
“…1,2 Abnormal lipoprotein metabolism has been implicated as a possible cause of these complications because of its potential role in immune system activation. [3][4][5][6] Cumulative data based on atherosclerotic experimental models suggest that CD4 ϩ T cells are present within plaques from initial stages of the disease. [7][8][9] They are mainly CD4 ϩ T-helper cells with a phenotype characteristic of the proinflammatory T-helper 1 (Th1) subset.…”
mentioning
confidence: 99%
“…13 It has been shown that in chronic renal disease, the protective effects of HDL-C are depressed not only due to the decrease of HDL-C concentration but also due to the alterations in its composition and antioxidant activity. 14 There is limited evidence concerning the comparison of oxLDL concentration in patients treated with different modes of dialysis, 15 although there are few studies about the comparison of antibodies against oxLDL in dialysis subgroups of patients. Also to our knowledge, the effect of hemodialysis (HD) on distribution of HDL subclasses in serum has been studied recently [16][17][18][19][20] but no data about the effect of peritoneal dialysis (PD) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in uremic patients, oxLDL seem to play a specific role in the frequencies and phenotypes of CD4 + /CD25 + /CD127¯ Tregs, which distinctly discriminates between nTreg and effector cell subsets [15]. Indeed, in these patients, oxLDL inhibit CD25 expression at the cell surface, whereas the expression of CD3 and CD4 (constitutively expressed on T cells), CD69 (early activation antigen) and HLA-DR (late activation antigen) is unchanged [9,15,41]. Thus oxLDL do not alter the steps of the signalling pathways triggering CD69 and HLADR expression, but mild oxidation of LDL is sufficient to dramatically disturb CD25 expression as demonstrated in a recent study [15].…”
Section: Effects Of Uremia and Oxldl On Cd4 + /Cd25¯ T Cellsmentioning
confidence: 99%
“…Overexpression of Fas sensitizes cells to Fas-induced apoptosis, suggesting that increased clustering of Fas on the plasma membrane results in a stronger ability to recruit procaspase-8, which would overcome the sequestering of procaspase-8 by Bcl-2, and could influence the inhibitory function of Bcl-2 or Bcl-xL on Fas-induced apoptosis [51]. Moreover, experiments with blocking antibodies to Fas suggest that mildly oxidized LDL acts mainly by up-regulating expression of Fas [9]. Activation of the Fas pathway results in oligomerization of Fas and recruitment of Fas-associated death domain (FADD) and FADD homologous, IL-1 beta-converting enzyme (ICE)-like protease (FLICE), which then activate caspases.…”
Section: Place Of Oxldl In Tregs Apoptosis In Pa-tients With Eskdmentioning
confidence: 99%
See 1 more Smart Citation